Primitive Extracellular Lipid Components on the Surface of the Charophytic Alga Klebsormidium flaccidum and Their Possible Biosynthetic Pathways as Deduced from the Genome Sequence - Kondo, Satoshi; Hori, Koichi; Sasaki-Sekimoto, Yuko; Kobayashi, Atsuko; Kato, Tsubasa; Yuno-Ohta, Naoko; Nobusawa, Takashi; Ohtaka, Kinuka; Shimojima, Mie; Ohta, Hiroyuki (Frontiers in Plant Science, 2016)
Klebsormidium flaccidum is a charophytic alga living in terrestrial and semiaquatic environments. K. flaccidum grows in various habitats, such as low-temperature areas and under desiccated conditions, because of its ability to tolerate harsh environments. Wax and cuticle polymers that contribute to the cuticle layer of plants are important for the survival of land plants, as they protect against those harsh environmental conditions and were probably critical for the transition from aquatic microorganism to land plants. Bryophytes, non-vascular land plants, have similar, but simpler, extracellular waxes and polyester backbones than those of vascular plants. The presence of waxes in terrestrial algae, especially in charophytes, which are the closest algae to land plants, could provide clues in elucidating the mechanism of land colonization by plants. Here, we compared genes involved in the lipid biosynthetic pathways of Arabidopsis thaliana to the K. flaccidum and the Chlamydomonas reinhardtii genomes, and identified wax-related genes in both algae. A simple and easy extraction method was developed for the recovery of the surface lipids from K. flaccidum and C. reinhardtii. Although these algae have wax components, their surface lipids were largely different from those of land plants. We also investigated aliphatic substances in the cell wall fraction of K. flaccidum and C. reinhardtii. Many of the fatty acids were determined to be lipophilic monomers in K. flaccidum, and a Fourier transform infrared spectroscopic analysis revealed that their possible binding mode was distinct from that of A. thaliana. Thus, we propose that K. flaccidum has a cuticle-like hydrophobic layer composed of lipids and glycoproteins, with a different composition from the cutin polymer typically found in land plant cuticles.